Open photoacoustic cell for thermal diffusivity measurements of a fast hardening cement used in dental restoring - Astrath, F. B. G.; Astrath, N. G. C.; Baesso, M. L.; Bento, A. C.; Moraes, João Carlos Silos [UNESP]; Santos, A. D. [UNESP] (American Institute of Physics (AIP), 2012)
Thermal diffusivity and conductivity of dental cements have been studied using open photoacoustic cell (OPC). The samples consisted of fast hardening cement named CER, developed to be a root-end filling material. Thermal characterization was performed in samples with different gel/powder ratio and particle sizes and the results were compared to the ones from commercial cements. Complementary measurements of specific heat and mass density were also performed. The results showed that the thermal diffusivity of CER tends to increase smoothly with gel volume and rapidly against particle size. This behavior was linked to the pores size and their distribution in the samples. The OPC method was shown to be a valuable way in deriving thermal properties of porous material. (C) 2012 American Institute of Physics. [doi: 10.1063/1.3673873]